Relationship of Bone Mineral Density to Progression of Knee Osteoarthritis. Issue 6 (30th May 2013) - Lee, Ji Y.; Harvey, William F.; Price, Lori L.; Paulus, Jessica K.; Dawson‐Hughes, Bess; McAlindon, Timothy E.
Abstract : Objective: To evaluate the longitudinal relationship between bone mineral density (BMD) and BMD changes and the progression of knee osteoarthritis (OA), as measured by cartilage outcomes. Methods: We used observational cohort data from the Vitamin D for Knee Osteoarthritis trial. Bilateral femoral neck BMD values as well as knee magnetic resonance imaging (MRI) scans in each subject were obtained at baseline and subsequently at 12 months and 24 months. The change in total cartilage volume and tibial and femoral cartilage thickness was measured by manual cartilage segmentation of 2 sequential knee MRI scans in each subject. Multivariable linear regression models were used to examine the associations of baseline BMD and BMD change with the cartilage outcomes, adjusting for baseline age, sex, body mass index, malalignment, and vitamin D treatment. Model fit and assumptions were validated. Results: A total of 127 subjects were eligible for analysis. Longitudinal BMD loss was associated with loss of cartilage volume (β = 1.25 per 0.1 gm/cm 2, P = 0.02) and loss of tibial cartilage thickness (β = 0.028, P = 0.03). BMD loss of a magnitude greater than the least significant change (<−4.7%) was associated with 1.02% cartilage volume loss per year ( P = 0.005), 0.014 mm femoral cartilage thickness loss ( P = 0.04), and 0.021 mm tibial cartilage thickness loss per year ( P = 0.009). There were no significant associations between baseline BMD and any of the cartilage outcomes. Conclusion: Longitudinal BMD loss is associated with progressive cartilage loss in knees with OA. Further work to clarify the basis of this relationship could reveal novel therapeutic targets for knee OA.